Using Word Mapping Technique to Improve the Students’ Speaking Ability on Hortatory Exposition Text At SMAN 3 Merbau - Dedy Safrizal Dedy Safrizal; Fakhri Ras Fakhri Ras; Masyhur Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This classroom action research was aimed to find out if Word Mapping technique in Brainstorming can improve the speaking ability of the students on Hortatory Exposition Text at grade XI Science Class 1 of SMAN 3 Merbau. The participants of this research were all of the students grade XI Science Class 1 of SMAN 3 Merbau (28 students).The procedures applied were: (a) explaining the objective of the learning, the teaching material, material, the text type; hortatory exposition, and the steps in using the technique, (b) dividing students into some groups of discussion and the teacher delivered the learning instruments needed such as flip chart and markers, (c) explaining about Hortatory Exposition Text to the students, (d) choosing the topic together, (e) asking asked to work in their group in limited time to generate ideas related to the topic as many as possible, (f) facilitating students in discussion, and (g) presenting the ideas in front of the class. The data were collected by using tests, observation sheets, and field notes. The level of achievement in this research was 70, based on the standard minimum criteria of achievement of English subject in SMAN 3 Merbau. The research finding showed that the implementation of Word Mapping technique could improve students’ speaking ability both at the first and second cycle. Based on the data analysis, the students’ score improved from 39,66 in the pre-test, to 56,72 in post-test 1, and up to 72,16 in post-test II. Therefore, the implementation of Word Mapping technique could improve students’ speaking ability on Hortatory Exposition text at SMAN 3 Merbau. Keywords: Word Mapping Technique, Speaking Ability, Hortatory Exposition Text.